IDDF2022-ABS-0213 Gastric intestinal metaplasia may attenuate reflux symptoms – analysis of a large observational prospective cohort. (2nd September 2022) - Tang, Si-Ying; Lee, Jonathan; Koh, Calvin J; Zhu, Feng; So, Jimmy; Ho, Khek-Yu; Srivastava, Supriya; Tsao, Stephen; Khor, Christopher; Fock, Kwong-Ming; Lim, Wee-Chian; Ling, Khoon-Lin; et al.
Abstract : Background: Gastric intestinal metaplasia (GIM) is a precancerous lesion associated with dysplasia and gastric cancer (GC). Annually, 1.8%, 10% and 73% of patients with atrophic gastritis, GIM and dysplasia progress to GC. While dyspepsia is associated with Helicobacter Pylori and active gastritis, GIM is not thought to be associated with specific symptoms. The aim of the study is to evaluate the correlation between GIM and pre-endoscopy symptoms. Methods: 2874 participants underwent 7480 gastroscopies with updated Sydney System gastric mucosal sampling from January 2004 – December 2010 with GIM graded using the Operative Link in Gastric Intestinal Metaplasia (OLGIM) staging. Prior to each endoscopy, the participants completed a medical history interview reporting symptoms of dyspepsia, acid brash, heartburn, dysphagia, nausea, vomiting, early satiety, indigestion, loss of weight, loss of appetite, coffee ground vomitus and melena. Results were compiled and statistics calculated using R for chi-square and logistic regression analysis. Results: GIM was present in 53.3% (n=3992) of the gastroscopies. One-third of the patients (37.1%, n=2781) were symptomatic prior to the endoscopy, with the most common symptoms being dyspepsia (n=1860, 24.9%), acid brash (n=838, 11.2%) and heartburn (n=520, 7%). Compared to controls, patients with GIM have lower proportions of symptoms (34.2% vs 39.8%, p<0.01). Of note, patients with GIM reported significantly less acid brash (9.5% vs 12.7%, p<0.01) and heartburn (5.2% vs 8.5%, p<0.01) (IDDF2022-ABS-0213 Table1), whereby H. pylori status was not significantly different in these subgroups. Conclusions: We hypothesize that patients with intestinal metaplasia and atrophic gastritis may have less acid secretion, and correspondingly fewer reflux symptoms. Although many patients in clinical practice, are scoped for dyspepsia and reflux symptoms, our data suggest that patients with GIM are less likely to have these symptoms and yet harbour this pre-malignant condition of the stomach.